Analisis Perubahan Kondisi Ekonomi UMKM di Desa Way Huwi Kabupaten Lampung Selatan Sebelum dan Saat Pandemi Covid-19 (Studi Kasus UMKM di Sekitar ITERA Desa Way Hui Kecamatan Jati Agung) - Chendy Aurellya; Arivina Ratih Yulihar Taher (Departement of Mathematics Education, 2023)
This research aims to determine the effect of the Covid-19 pandemic on turnover, profits and capital of MSMEs in Way Huwi Village before and during the pandemic. The population studied included 266 food businesses in the village. The purposive sampling method was used with 71 food traders as samples. Data was collected through interviews, documentation, financial reports and literature studies. Analysis was carried out using IBM SPSS 28 for Windows. The test results show that turnover, profits and capital of MSMEs show significant differences before and during the pandemic. This is shown through the Wilcoxon rank test because the data is not normally distributed.